A community-based gastroenteritis outbreak after Typhoon Haiyan, Leyte, Philippines, 2013 - Ventura, Ray Justin; Muhi, Edzel; de los Reyes, Vikki Carr; Sucaldito, Ma Nemia; Tayag, Enrique (Western Pacific Surveillance and Response, 2015)
Background: Three weeks after Typhoon Haiyan, an increasing number of acute gastroenteritis cases were reported in Kananga, Leyte, an area where evacuated residents had returned home two days after the disaster. An outbreak investigation was conducted to identify the source and risk factors associated with the increase of gastroenteritis.Methods: A case was defined as any person in Kananga who developed acute diarrhoea (>= 3 times/24 hours) and any of the following symptoms: fever, nausea, vomiting or abdominal pain from 11 November 2013 to 10 December 2013. Active case finding was conducted by reviewing medical records, and a case-control study was conducted. Rectal swabs and water samples were tested for bacteriological examination.Results: One hundred and five cases were identified. Multivariate analysis revealed that consumption of untreated drinking-water was associated with illness (adjusted odds ratio: 18.2). Both rectal swabs and municipal water samples tested positive for Aeromonas hydrophila. On inspection of the municipal water system, breaks in the distribution pipes were found with some submerged in river water.Conclusion: This acute gastroenteritis outbreak was most likely caused by Aeromonas hydrophila and transmitted through a contaminated water source. This study highlights that areas less damaged by a disaster that do not require ongoing evacuation centres can still have acute gastroenteritis outbreaks. All affected areas should be monitored during a disaster response, not just those with evacuation centres. Boiling or chlorinating of water should also be recommended for all areas affected by disaster.